2003
DOI: 10.1046/j.1365-2141.2003.04545.x
|View full text |Cite
|
Sign up to set email alerts
|

Stromal‐derived factor 1 and matrix metalloproteinase 9 levels in bone marrow and peripheral blood of patients mobilized by granulocyte colony‐stimulating factor and chemotherapy. Relationship with mobilizing capacity of haematopoietic progenitor cells

Abstract: Summary. The roles of the chemokine stromal-derived factor 1 (SDF-1) and the matrix metalloproteinase 9 (MMP-9) in haematopoietic progenitor cell (HPC) mobilization are still unclear, particularly when patients are mobilized by granulocyte colony-stimulating factor (G-CSF) plus chemotherapy. We determined bone marrow (BM) and peripheral blood (PB) plasma levels of SDF-1, together with CXC-chemokine receptor 4 (CXCR-4) expression on CD34 + cells, and interleukin 8 (IL-8) and MMP-9 in 55 patients mobilized for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 50 publications
3
29
0
1
Order By: Relevance
“…Furthermore, we also found that MMP inhibitor not only inhibited the SDF-1 degradation in BM, but also significantly decreased the number of WBC and CFC in the BALB/c mice PB. Although other data show that G-CSF-induced HSPC mobilization involves MMP-9, without reversing the positive gradient of SDF-1 between BM and PB, 34 our data suggested that disappearance of SDF-1 between BM and PB was related to the degrading activity of MMP-9, and MMP-9-dependent SDF-1-degradation might be a crucial step in HSPC mobilization.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, we also found that MMP inhibitor not only inhibited the SDF-1 degradation in BM, but also significantly decreased the number of WBC and CFC in the BALB/c mice PB. Although other data show that G-CSF-induced HSPC mobilization involves MMP-9, without reversing the positive gradient of SDF-1 between BM and PB, 34 our data suggested that disappearance of SDF-1 between BM and PB was related to the degrading activity of MMP-9, and MMP-9-dependent SDF-1-degradation might be a crucial step in HSPC mobilization.…”
Section: Discussionmentioning
confidence: 62%
“…We have recently reported that the uPAR-derived peptide uPAR 84-95 stimulates migration of human CD34 + KG1 cells and CD34 + HSCs, by activating fMLP receptors, and inactivates CXCR4, the chemokine receptor primarily responsible for HSC retention in bone marrow (6,(22)(23)(24)(25). We then investigated whether the same peptide is able to exert the same effects on mouse CD34 + M1 leukemia cells.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we and others 13,25,26 have observed a negative correlation between the mobilization capacity and CXCR4 expression on CD34 þ cells. Our previous study demonstrated that the number of haematopoietic progenitors in the peripheral blood correlated with the percent of CXCR4-negative CD34 þ cells in the leukapheresis product.…”
Section: Discussionmentioning
confidence: 99%